FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK SEKS PRANIKAH DI KALANGAN ANAK JALANAN KOTA SEMARANG TAHUN 2016 - Marshia Zefanya R.R; V.G Tinuk Istiarti; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2016)
The existence of street children in the city never disappeared completely. Also with the problems arising from the existence of street children, ranging from physical violence, sexual violence, to STIs that are often found on street children. According to data from DKK Semarang on 2014, there are 9 STDs cases and 104 unwanted pregnancy cases were found in children and adolescents on Semarang. This study aims to analyze factors associated with the practice of premarital sex on street children. This research is descriptive analytic with cross sectional design. The population in this study were street children who became targets of RPSA Emas Indonesia, with an age range between 12 to 17 years. The sampling technique used total population, with 55 respondents.Results from the study show that peer support factor associated with the practice of premarital sex (Pvalue = 0.006). Besides other factors not related to the practice of premarital sex is the knowledge of the practice of premarital sex (Pvalue = 0.166), attitude toward the practice of premarital sex (Pvalue = 0.743), access to information about premarital sex (Pvalue = 0.380), parenting parents as well (Pvalue = 0.320).Suggested for DKK Semarang to cooperate with RPSAs or related parties so that it can provide deeply information about the harmful effects of the practice of premarital sex. Then to Dinsospora Semarang, it is advisable to be able to reach street children who are already or nearly raised, to provide information on sex education. Thus the street children who are already provided can be a peer educator for their friend who was still difficult to reach by the department or RPSAs.